Prarancangan Pabrik Etil Formiat dari Asam Formiat dan Etanol dengan Kapasitas 60.000 Ton/Tahun - , SARFINA RAMADIANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Preliminary design of this ethyl formate plant is intended to asses the feasibility of this plant. Ethyl formate plant is designed to fulfill 60.000 ton/year of capacity and to be operated continuously 330 days/year. In order to gain the ethyl formate product as designed capacity, 40043,53 ton/year of ethanol 95% (w/w) and 40793,78 ton/year of formic acid 94% (w/w) are required as main raw materials. The sysntesis of ethyl formate is based on the esterification process and catalyzed by sulphuric acid. The reaction takes place in a reactive distillation column in atmospheric condition. Another distillation column is needed to further purify the ethyl formate product up to 98,6% (w/w) of concentration. To be constructed in Cilegon, Banten, this plant requires 12.000 m2 area and employs 216 labors. The consumed energy includes electricity of 1594607,09 kWh/year and 25604,08 m3/year of fuel oil. Moreover, the utility requires 26040,00 kg/hour of make-up water and 150 m3/hour of air instrument. Fixed capital costs $ 14,534,181.82 + Rp 88.444.256.897,33 and working capital costs $ 12,993,533.03 + Rp 239.401.583.121,16. Based on the economical feasibility study, this plant is classified as low risk chemical plant with 43,38% of ROI (before taxes)